Developing e-Book as English Learning Media for Deaf Students - Putra Pratama; Destia Dwi Mulyani (English Language in Focus (ELIF), 2022)
This Research and Development (R&D) study aimed to develop English e-book for 10th grade deaf students and measure the extent to which this e-book was valid, practical and effective to use as learning media. Three stages of R&D proposed by (Akker, 1990); analysis, design, evaluation and revision applied by the writers in developing that e-book. To measure the validity and practicality of this e-book, the criteria of (Tessmer, 1993) was used as the reference. Meanwhile, the effectiveness of this e-book was measured based on Minimum Mastery Criterion of English subject determined by the school. There were 4 experts, 2 English teachers, and 9 students with hard of hearing involved in this research work. The findings of this study revealed that the e-book developed by the writers reached the levels of ‘very high valid’ (4.45) and ‘very high practical’ (4.55). Additionally, this e-book was also found effective since the students’ English test results exceeded the Minimum Mastery Criterion of 72. Referring to these findings this research concluded that the English e-book developed by the writers was valid, practical, and effective to be utilized as English learning media for 10th grade students of hard of hearing.